Questioning performance measurement metrics, organizations and power - Redden, Guy (Sage swifts, 2019)
Questioning Performance Measurement: Metrics, Organizations and Power is the first book to interrogate the organizational turn towards performance metrics critically. Performance measurement is used to evaluate a diverse range of activities throughout the private, public and non-governmental sectors. But in an increasingly data driven world, what does it really mean to measure 'performance'? Taking a sociology of quantification perspective, this book traces the rise of performance measurement, questions its methods and objectivity, and examines the social significance of the flood of numbers through which value is represented and actors are held accountable. An illuminating read for students, scholars and practitioners across Organization Studies, Sociology, Business and Management, Public Policy and Administration. --Provided by publisher.